Desenvolvimento e estudo de estabilidade de suspensões de pirimetamina para uso pediátrico - Neis, Julya Sarmento (2023)
Toxoplasmosis is a zoonosis with worldwide distribution, which can be transmitted to the fetus during pregnancy. The child's treatment should start just after birth and consists of pyrimethamine (PYM), sulfadiazine, and folinic acid. However, PYM is commercially available only as tablets, which difficult the treatment of children. In this context, this study aimed to verify the feasibility of obtaining oral suspensions of PYM, suitable for all pediatric age groups. Two PYM suspensions were prepared: suspension A (with preservative, methylparaben - MP) and suspension B (without preservative), from commercially obtained tablets. The excipients and their concentrations were carefully chosen to obtain safe products for the intended age group. Physicochemical characteristics such as pH, particle size, zeta potential, viscosity, dissolution, and PYM and (MP) content were evaluated using an ultraperformance liquid chromatography (UPLC) method validated during the study, following the current guidelines. Concerning the microbiological evaluation, the count of mesophilic microorganisms and the absence of E. coli were determined. For the stability study, suspension A was evaluated for 42 days, stored under refrigeration or at room temperature (20 to 25ºC). Suspension B was kept under refrigeration and analyzed for 7 days. The results obtained indicated that the CLUE method was accurate, precise, linear, robust, specific, and suitable for use in stability studies. The formulations showed pH values in the range of 7.1 to 7.9, particle size in the range of 50 to 65 µm, and zeta potential in the range of -50 to -65 mV; these characteristics remained constant throughout the study. The formulations were characterized as non-Newtonian fluids, with pseudoplastic behavior, presenting thixotropy. In addition, there was a decrease in the formulation viscosity in the final analysis. The formulation dissolution was greater than 90% at 30 minutes, remaining constant throughout the study. There was a small decrease in PYM and MP levels throughout the study, with no evidence of a significant difference considering the initial time. Regarding the bioburden, suspension A, under both storage conditions, met the pharmacopeial specification, with bacterial and fungal counting < 10 CFU/mL and an absence of E. coli until the end of the study. Suspension B, in turn, met the requirements of bacteria and fungi count until the 4th day. Regarding E. coli, there was no growth until the 7th day. The results indicated the viability of obtaining the formulation; suspension A showed physicochemical and microbiological stability for 42 days, using a single preservative at a low concentration. Suspension B, focused on the treatment of neonates, can be used for up to four days without impairing the physicochemical characteristics and without microbial contamination. Both formulations are alternatives for the treatment of congenital toxoplasmosis.